2020
DOI: 10.5603/fm.a2019.0071
|View full text |Cite
|
Sign up to set email alerts
|

Internal carotid and vertebral arteries diameters and their interrelationships to sex and left/right side

Abstract: Background: The available anatomical data about diameters of inflow vessels to the circle of Willis reflect various diagnostic and imaging methods used, sample sizes, levels of measurements, and lack of possible specific ethnic, regional or genetic data. Additionally, the data are often without distinctions about left-right or sex. Materials and methods: Therefore, using computed tomography angiography (CTA) we investigated diameters of internal carotid (ICA) and vertebral (VA) arteries in 70 adult persons (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Fourth, the sample sizes of many of the above studies were small, which increases the likelihood of sampling errors. We found that the inner diameters of the bilateral CS and distal CCA were greater in males than females, consistent with observations reported by several prior investigations using CTA, ultrasonography, or MRA [22,24,[26][27][28][29]. One possible reason for the larger vessel diameters in males than females is that men have, on average, a larger body size.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Fourth, the sample sizes of many of the above studies were small, which increases the likelihood of sampling errors. We found that the inner diameters of the bilateral CS and distal CCA were greater in males than females, consistent with observations reported by several prior investigations using CTA, ultrasonography, or MRA [22,24,[26][27][28][29]. One possible reason for the larger vessel diameters in males than females is that men have, on average, a larger body size.…”
Section: Discussionsupporting
confidence: 91%
“…An interesting observation of this analysis was that the inner diameters of the CS and distal CCA were larger on the right side than on the left side. Several published studies have also reported a larger luminal diameter for the right CCA than for the left CCA [24,27], although not all authors agree [22,28,29]. In view of the clear variation between left and right sides in this study, which included a large number of participants and used a technique with a high spatial resolution (3D-DSA), the failure of some other studies to detect such differences may be related to smaller sample size (which would reduce the power of the analysis) and use of methods with poorer spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in subadventitia might be, presumably, more often in intracranial VAD, which was not noted in our study [30,31]. However, we must remember that there are other plausible explanations for the higher count of occlusions, such as lower lumen or lower blood flow velocity in vertebral arteries [32].…”
Section: Radiological Findings and Long-term Outcomesmentioning
confidence: 48%
“…Топлотни таласи утичу и на повећање смртности, док ће погоршање климатских услова довести до учесталијих промјена и погоршања здравствене ситуације код најтежих болесника. Ријеч је о обољењима са кардиоваскуларним и неуролошким ризицима, алергијским реакцијама и другим акутним реакцијама на високе дневне температуре ваздуха, а могу се јавити и други здравствени проблеми као што су болести изазване бактеријама у храни и води, болести које преносе комарци и птице и друго (Miljković et al 2011;Vujkovic et al 2012;Vulic et al 2019;Škrbić et al 2019;Spasojević et al 2020)…”
Section: климатске промјене и здравље у републици српској и босни и х...unclassified